Seasonal calving in European Prehistoric cattle and its impacts on milk availability and cheese-making - Balasse, Marie; Gillis, Rosalind; Živaljević, Ivana; Berthon, Rémi Jean-Paul; Kovačiková, Lenka; Fiorillo, Denis; Arbogast, Rose-Marie; Bălăşescu, Adrian; Bréhard, Stéphanie; Nyerges, Éva Á.; Dimitrijević, Vesna; Bánffy, Eszter; et al. (Scientific reports, 2021)
Present-day domestic cattle are reproductively active throughout the year, which is a major asset for dairy production. Large wild ungulates, in contrast, are seasonal breeders, as were the last historic representatives of the aurochs, the wild ancestors of cattle. Aseasonal reproduction in cattle is a consequence of domestication and herding, but exactly when this capacity developed in domestic cattle is still unknown and the extent to which early farming communities controlled the seasonality of reproduction is debated. Seasonal or aseasonal calving would have shaped the socio-economic practices of ancient farming societies differently, structuring the agropastoral calendar and determining milk availability where dairying is attested. In this study, we reconstruct the calving pattern through the analysis of stable oxygen isotope ratios of cattle tooth enamel from 18 sites across Europe, dating from the 6th mill. cal BC (Early Neolithic) in the Balkans to the 4th mill. cal BC (Middle Neolithic) in Western Europe. Seasonal calving prevailed in Europe between the 6th and 4th millennia cal BC. These results suggest that cattle agropastoral systems in Neolithic Europe were strongly constrained by environmental factors, in particular forage resources. The ensuing fluctuations in milk availability would account for cheese-making, transforming a seasonal milk supply into a storable product.
Gesehen am 16.06.2021